Low field magneto-resistive anisotropy in polycrystalline Sm0.55Sr0.45MnO3. (September 2015) - Egilmez, M.; Chow, K.H.; Jung, J.
Abstract: Longitudinal and transverse magnetoresistance of polycrystalline Sm0.55 Sr0.45 MnO3 are measured in order to study anisotropic magneto-transport (AMR) properties as a function of grain boundary density. It is found that the magnitude of the AMR strongly depends on the grain size and the magnetic moment of the samples. The results are explained through a spin polarized transport model in which the difference between the magnetization within the grain and at its surface determines the tunneling probability of the spin polarized carriers and the anisotropic magnetoresistance. Our results show that the relationship between the AMR and magnetic moment in manganites is rather simple and is as expected as in the 3d alloys. Highlights: We report magneto-resistive anisotropy (AMR) in Sm0.55 Sr0.45 MnO3 . Magnetic moment of the grain and its surface determines the AMR. AMR is strongly dependent on grain size and magnetic moment of the specimen. AMR is linearly proportional to the magnetic moment.